Influence of direct and staggered sowing of pelleted onion (Allium cepa) seeds on various seed yield parameters under Asian mid-hill conditions - SHARMA, PALAK; KUMAR, MANISH; VERMA, ROHIT (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during 2021–22 and 2022–23 at Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to study the impact of precision planting (using pelleted seeds) and sowing dates on the numerous attributes of the onion (Allium cepa L.) variety Palam Lohit. The study was carried out with the objective to determine whether direct seed sowing would lead to successful seed production in onion under mid-hill conditions (which is not the conventional practice). Also, the staggered sowing dates would help to determine the best sowing time for higher seed production. The experiment was laid in randomized block design (Factorial) (F-RBD) with 3 replications having 19 treatments, including 3 pelleting treatments, viz. P1 (wood ash); P2 (ZnSO4 + wood ash); and P3 (H3BO3 + wood ash); 6 sowing dates, viz. D1 (15th September); D2 (1st October); D3 (15th October); D4 (1st November); D5 (15th November); and D6 (1st December); and Da (traditional bulb planting as control). The study revealed that seed pelleting with ZnSO4 + wood ash and early sowing (15th September) gave best results in terms of emergence (%), plant height, number of seeds/umbel and number of seeds/plant, seed yield and 1000-seed weight. The direct sowing treatments produced seeds in one year as opposed to two years using the conventional bulb planting method, which is traditionally being used in the Asian mid-hills.